Modified antifriction and antiwear carbon fiber based on self-assembly, self-lubricating material containing modified fiber and preparation method of self-lubricating material

By self-assembling the organic outer coat layer formed by cyclodextrin and sodium dodecyl sulfate nanosheets on the surface of the carbon fiber, the scratching and wear problems of carbon fiber in the lubrication system are solved, and efficient friction reduction and anti-wear performance is improved, and simplified The preparation process is carried out and the mechanical properties of the material are maintained.

CN119194854AActive Publication Date: 2024-12-27TSINGHUA UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411289909.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Carbon fibers have severe scratches caused by surface hard particles in mechanical lubrication systems, which weakens the lubrication effect and increases wear. The existing modification methods are complex and affects strength, and fail to effectively improve friction reduction and wear resistance.

Method used

Using modified anti-wear carbon fibers based on self-assembly, nanosheets formed by cyclodextrin and sodium dodecyl sulfate coated the surface of the carbon fiber to form an organic outer coat layer, reduce surface modulus, improve surface activity and interface bonding strength , a lubricating film is formed to reduce friction and wear.

Benefits of technology

Significantly reduce the friction coefficient and wear rate, improve the overall friction reduction and anti-wear properties of self-lubricating materials, avoid the use of strong acids or toxic chemical reagents, simplify the preparation process, and maintain the mechanical properties and interface bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194854A_ABST
    Figure CN119194854A_ABST
Patent Text Reader

Abstract

The invention discloses a modified antifriction and antiwear carbon fiber based on self-assembly, a self-lubricating material containing the modified fiber and preparation methods of the modified antifriction and antiwear carbon fiber and the self-lubricating material. The modified antifriction and antiwear carbon fiber based on self-assembly comprises carbon fiber and an organic coating layer formed on the surface of the carbon fiber, and the organic coating layer comprises nanosheets formed by cyclodextrin and lauryl sodium sulfate. The self-lubricating material containing the modified fibers comprises 5-20% of the self-assembly-based modified antifriction and antiwear carbon fibers, 0-10% of polytetrafluoroethylene fibers and more than 70% of an epoxy resin matrix. The modified antifriction and antiwear carbon fiber based on self-assembly can improve the antifriction and antiwear performance of a self-lubricating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to modified antifriction and wear-resistant carbon fibers based on self-assembly, a self-lubricating material containing the modified fibers and a preparation method thereof, and belongs to the technical field of carbon fiber surface modification. Background Art

[0002] Carbon fiber has become an important structural material and functional material in resin-based composite materials due to its high strength, superior specific modulus, heat transfer performance, low friction coefficient, and wide temperature resistance. However, in some mechanical lubrication systems, carbon fiber has a high surface modulus, and the presence of some hard particles on its surface will cause very serious scratches on the friction pair. While carbon fiber enhances the mechanical properties of the matrix, it greatly weakens the friction reduction effect of the lubrication phase, and further aggravates the process of abrasive wear and adhesive wear, and even causes the failure of the mechanical system, resulting in irreparable losses.

[0003] In recent years, researchers have modified the surface of carbon fibers physically or chemically to address various problems on the surface of carbon fibers. The modification methods usually include chemical grafting, physical coating, high-energy radiation, etc. The operation process of these methods is often cumbersome and complicated. While improving the surface performance of carbon fibers, they also affect the strength of the body. Moreover, these modification methods are generally used to solve the problem of poor interfacial bonding between carbon fibers and the matrix. By strengthening the interaction between carbon fibers and the matrix, the bonding effect between carbon fibers and the matrix is ​​improved, thereby improving the application value of carbon fibers in engineering. As for the surface modification of carbon fibers to enhance the anti-friction and anti-wear properties of the matrix, there is still a lack of relevant reports in this field. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a modified anti-friction and anti-wear carbon fiber based on self-assembly, a self-lubricating material containing the modified fiber and a preparation method thereof. The modified anti-friction and anti-wear carbon fiber based on self-assembly of the present invention can improve the anti-friction and anti-wear performance of the self-lubricating material.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a modified friction-reducing and wear-resistant carbon fiber based on self-assembly, which includes: carbon fiber, and an organic coating layer formed on the surface of the carbon fiber, the organic coating layer including nanosheets formed by cyclodextrin and sodium dodecyl sulfate; wherein the mass ratio of the carbon fiber to the organic coating layer is 8:1 to 10:1.

[0006] According to a specific embodiment of the present invention, preferably, the diameter of the carbon fiber is 5-10 μm.

[0007] According to a specific embodiment of the present invention, preferably, the average thickness of the organic coating layer is 20 to 60 nm.

[0008] According to a specific embodiment of the present invention, preferably, the molar ratio of cyclodextrin to dodecyl sulfate in the nanosheets formed by cyclodextrin and sodium dodecyl sulfate is 1.8:1 to 2.2:1.

[0009] According to a specific embodiment of the present invention, preferably, the nanosheets formed by the cyclodextrin and sodium dodecyl sulfate have a planar size of 1 to 20 μm and a thickness of 1 to 8 nm.

[0010] The second aspect of the present invention provides a method for preparing the above-mentioned modified antifriction and wear-resistant carbon fiber based on self-assembly, which comprises the following steps:

[0011] The carbon fiber is immersed in a nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate, wherein the solvent in the nanosheet solution is a first solvent, which is a good solvent for the nanosheet, and then a second solvent is added dropwise, which is a poor solvent for the nanosheet. The solution is allowed to stand, and the nanosheets formed by cyclodextrin and sodium dodecyl sulfate spontaneously settle and precipitate on the surface of the carbon fiber, assemble to form an organic coating layer, and obtain the modified anti-friction and wear-resistant carbon fiber based on self-assembly.

[0012] According to a specific embodiment of the present invention, preferably, the carbon fiber is desizing carbon fiber, and the desizing comprises: placing the carbon fiber in ethanol and ultrasonically treating it at 30 to 60° C. for 2 to 4 hours, then washing the ethanol-treated carbon fiber with water, and then vacuum drying it at 80 to 120° C. for 12 to 24 hours to obtain the desizing carbon fiber.

[0013] According to a specific embodiment of the present invention, preferably, the preparation step of the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate includes: adding cyclodextrin and sodium dodecyl sulfate to a first solvent, stirring, spontaneously assembling into nanosheets formed by cyclodextrin and sodium dodecyl sulfate, and then freeze-drying to obtain nanosheet powder, and then using the first solvent to prepare the nanosheet powder into a solution to obtain the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate. Among them, more preferably, the molar ratio of the cyclodextrin and the sodium dodecyl sulfate is 1.8:1 to 2.2:1. More preferably, the stirring conditions include: stirring at a speed of 300 to 800 rpm for 12 to 24 hours at 40 to 70 ° C. More preferably, the concentration of the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate is 1 to 6 mg / mL.

[0014] According to a specific embodiment of the present invention, preferably, the mass ratio of the carbon fiber to the nanosheets formed by cyclodextrin and sodium dodecyl sulfate is 5:(0.1-1.5).

[0015] According to a specific embodiment of the present invention, preferably, the volume ratio of the nanosheet solution formed by the cyclodextrin and sodium dodecyl sulfate to the second solvent is 1:2 to 2:1.

[0016] According to a specific embodiment of the present invention, preferably, the standing time is 2 to 8 hours.

[0017] The third aspect of the present invention provides a self-lubricating material containing modified fibers. Taking the total mass of the self-lubricating material containing modified fibers as 100%, the self-lubricating material comprises: 5-20% of the modified anti-friction and wear-resistant carbon fibers based on self-assembly, 0-10% of polytetrafluoroethylene fibers and more than 70% of an epoxy resin matrix.

[0018] A fourth aspect of the present invention provides a method for preparing the above-mentioned self-lubricating material containing modified fibers, which comprises the following steps:

[0019] The modified antifriction and wear-resistant carbon fiber based on self-assembly and the selectively added polytetrafluoroethylene fiber are added to a mixture of epoxy resin prepolymer and curing agent, mixed evenly, poured into a mold, and cured to obtain the self-lubricating material containing the modified fiber.

[0020] According to a specific embodiment of the present invention, preferably, the curing includes two stages of curing, the first stage of curing is curing at 60-100° C. for 2-5 hours, and the second stage of curing is curing at 100-140° C. for 2-5 hours.

[0021] The present invention has at least the following beneficial effects:

[0022] (1) The present invention uses nanosheets formed by cyclodextrin and sodium dodecyl sulfate to coat the surface of carbon fiber to form an organic coating layer, which plays a role in reducing friction and resisting wear. The mechanism can be attributed to the synergistic effect of multiple factors. First, SCD (nanosheets formed by cyclodextrin and sodium dodecyl sulfate) is a layer of organic nanocoat. Unlike the inorganic coating in the prior art (such as MoS2 nanosheets grown on the surface of carbon fiber, or flaky nickel-cobalt bimetallic hydroxides, etc.), the organic nanocoat of the present invention is relatively soft. It coats the hard particles with high modulus on the surface of carbon fiber, reduces the surface modulus of carbon fiber, makes its surface area milder, and reduces the damage of sharp and rough particles to the friction film during relative motion, which is conducive to forming a more stable, complete and continuous transfer film, avoiding direct contact between the contact pair rough peaks, and achieving low friction and wear through interlayer shear of the lubricating film. Secondly, the nanosheet containing hydroxyl is introduced into the surface of carbon fiber to improve its surface activity and roughness, and the chemical action and mechanical interlocking improve the interface bonding strength between carbon fiber and matrix, reduce the interface failure problems such as debonding and pulling out of carbon fiber, so as to make the integration degree of self-lubricating material higher, reduce the adhesive wear and abrasive wear caused by the formation of large pieces of wear debris in the friction and wear process. Thirdly, although the organic nano coat of the present invention reduces the modulus of carbon fiber surface, it does not affect the overall hardness of self-lubricating material, and the hardness is slightly improved after modification, which is also conducive to improving wear resistance. In addition, during the friction process, SCD will decompose into multiple molecular fragments to interact with polytetrafluoroethylene and the stainless steel ball of the friction pair, forming FO bonds and metal organic compounds, which act like alcohol lubricants, thereby forming a rich mixed lubricating film at the interface, and, since there is no strong polar group in SCD, the adhesion ability to metal is poor, which improves the anti-adhesion of lubricating film instead, thereby reducing the wear debris attached to the surface of the steel ball and improving the quality of the surface of the steel ball. Therefore, the present invention assembles SCD on the surface of carbon fiber, thereby effectively improving the friction reduction and anti-wear performance of the self-lubricating material, which is mainly the effect brought about by the synergistic effect of physical coating and surface chemical composition.

[0023] (2) The method for preparing the modified anti-friction and anti-wear carbon fiber based on self-assembly of the present invention is simple and efficient, and avoids the complicated process of using strong acid or other toxic and dangerous chemical reagents for treatment, and is environmentally friendly, non-toxic and harmless. Moreover, the present invention adopts a two-step method to prepare the modified anti-friction and anti-wear carbon fiber based on self-assembly, first preparing nanosheets formed by cyclodextrin and sodium dodecyl sulfate, and then assembling them on the surface of the carbon fiber to form an organic coating layer. This preparation method can more accurately control the size of the nanosheets on the surface of the carbon fiber, and can better control the content of the nanosheets assembled on the surface of the carbon fiber, and has the advantages of strong operability and strong adjustability.

[0024] (3) The self-lubricating material containing the modified anti-friction and anti-wear carbon fiber based on self-assembly of the present invention has a significantly lower friction coefficient compared to the self-lubricating material without the modified anti-friction and anti-wear carbon fiber of the present invention, and the degree of reduction in wear rate can reach more than one order of magnitude. The modified carbon fiber of the present invention significantly improves the overall anti-friction and anti-wear performance of the self-lubricating material. Therefore, the use of the modified anti-friction and anti-wear carbon fiber based on self-assembly of the present invention can alleviate or avoid the situation in which the carbon fiber in the self-lubricating material is worn due to the hard particles on its surface scratching the friction pair.

[0025] (4) The modified anti-friction and anti-wear carbon fiber based on self-assembly of the present invention improves the anti-friction and anti-wear properties of the self-lubricating material without weakening the mechanical properties of the self-lubricating material and the interface bonding between the carbon fiber and the resin matrix. Instead, it slightly improves the two. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 These are SEM and TEM images of the desized carbon fiber in Example 1 and the modified friction-reducing and wear-resistant carbon fiber based on self-assembly.

[0027] Figure 2 These are thermogravimetric graphs of the desized carbon fiber in Example 1, the modified friction-reducing and wear-resistant carbon fiber based on self-assembly, and the nanosheets formed by cyclodextrin and sodium dodecyl sulfate.

[0028] Figure 3 SEM images of modified friction-reducing and wear-resistant carbon fibers based on self-assembly obtained by assembling SCD aqueous solutions of different concentrations on the CF surface.

[0029] Figure 4 This is the SEM image of the modified carbon fiber in Comparative Example 4.

[0030] Figure 5 Friction curves and average friction coefficients of self-lubricating materials with different CF-SCD contents.

[0031] Figure 6 It is the friction coefficient of the self-lubricating material of Example 1 and Comparative Examples 1-2.

[0032] Figure 7 is the average wear rate of self-lubricating materials with different CF-SCD contents.

[0033] Figure 8 The three-dimensional white light image and wear scar depth of the surface wear scar of self-lubricating materials with different CF-SCD contents.

[0034] Fig. 9 The wear scar morphology and depth of the self-lubricating materials of Example 1 and Comparative Examples 1-2.

[0035] Fig.10is the wear rate of the self-lubricating material of Example 1 and Comparative Examples 1-2.

[0036] Fig.11 The bending properties, tensile properties and compression properties of the self-lubricating materials and pure epoxy resins of Example 11 and Comparative Examples 6-7 are shown. DETAILED DESCRIPTION

[0037] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0038] It should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0040] According to a specific embodiment of the first aspect of the present invention, the present invention provides a modified friction-reducing and wear-resistant carbon fiber based on self-assembly, which includes: carbon fiber, and an organic coating layer formed on the surface of the carbon fiber, the organic coating layer includes nanosheets formed by cyclodextrin and sodium dodecyl sulfate; wherein the mass ratio of the carbon fiber to the organic coating layer is 8:1 to 10:1, for example but not limited to 8:1, 9:1 or 10:1, etc., preferably 9:1.

[0041] In some embodiments, the carbon fiber has a diameter of 5 to 10 μm.

[0042] In some embodiments, the average thickness of the organic coating layer is 20-60 nm.

[0043] In some embodiments, the molar ratio of cyclodextrin to dodecyl sulfate in the nanosheets formed by cyclodextrin and sodium dodecyl sulfate is 1.8:1 to 2.2:1, such as but not limited to 1.8:1, 2:1 or 2.2:1, etc., preferably 2:1.

[0044] In some embodiments, the nanosheets formed by the cyclodextrin and sodium dodecyl sulfate have a planar size of 1 to 20 μm and a thickness of 1 to 8 nm.

[0045] In some embodiments, the cyclodextrin is β-cyclodextrin.

[0046] According to a specific embodiment of the second aspect of the present invention, the present invention provides a method for preparing the above-mentioned modified anti-friction and anti-wear carbon fiber based on self-assembly, which comprises the following steps:

[0047] The carbon fiber is immersed in a nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate, wherein the solvent in the nanosheet solution is a first solvent, which is a good solvent for the nanosheet, and then a second solvent is added dropwise, which is a poor solvent for the nanosheet. The solution is allowed to stand, and the nanosheets formed by cyclodextrin and sodium dodecyl sulfate spontaneously settle and precipitate on the surface of the carbon fiber, assemble to form an organic coating layer, and obtain the modified anti-friction and wear-resistant carbon fiber based on self-assembly.

[0048] In some embodiments, the first solvent includes one or more of water, N,N-dimethylformamide and dimethyl sulfoxide, etc., which have good solubility in the nanosheets of the present invention. The second solvent includes one or more of acetone and tetrahydrofuran, etc., which have poor solubility in the nanosheets of the present invention.

[0049] In some embodiments, the carbon fiber is desizing carbon fiber, and the desizing includes: placing the carbon fiber in ethanol and ultrasonically treating it at 30-60°C for 2-4 hours, then repeatedly washing the ethanol-treated carbon fiber with deionized water, and then vacuum drying it at 80-120°C for 12-24 hours to obtain the desizing carbon fiber.

[0050] In some embodiments, the preparation step of the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate includes: adding cyclodextrin and sodium dodecyl sulfate to a first solvent, stirring, spontaneously assembling into nanosheets formed by cyclodextrin and sodium dodecyl sulfate, and then freeze-drying to obtain nanosheet powder, and then using the first solvent to prepare the nanosheet powder into a solution to obtain the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate. Preferably, the molar ratio of the cyclodextrin to the sodium dodecyl sulfate is 1.8:1 to 2.2:1. Preferably, the stirring conditions include: stirring at a speed of 300 to 800 rpm for 12 to 24 hours at 40 to 70 ° C. Preferably, the concentration of the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate is 1 to 6 mg / mL. The present invention can achieve directional control of the size of the nanosheet by regulating the concentration of the nanosheet solution, assembly time (i.e., stirring time) and other conditions. In addition, the nanosheets prepared by the method of the present invention also have the advantages of uniformity and isotropy.

[0051] In some embodiments, in the above preparation method, the mass ratio of the carbon fiber and the nanosheets formed by the cyclodextrin and sodium dodecyl sulfate is 5:(0.1-1.5), for example but not limited to 5:0.1, 5:0.5, 5:1, or 5:1.5.

[0052] In some embodiments, the volume ratio of the nanosheet solution formed by the cyclodextrin and sodium dodecyl sulfate to the second solvent is 1:2 to 2:1, for example but not limited to 1:2, 1:1 or 2:1.

[0053] In some embodiments, the standing time is 2 to 8 hours, for example but not limited to 2 hours, 4 hours, 6 hours or 8 hours.

[0054] In some embodiments, after the standing, conventional washing, vacuum drying and other steps may be performed. For example, deionized water may be used for repeated washing. The vacuum drying temperature may be 80 to 100° C. and the time may be 12 to 24 hours.

[0055] According to a specific embodiment of the third aspect of the present invention, the present invention provides a self-lubricating material containing modified fibers, which comprises, based on the total mass of the self-lubricating material containing modified fibers as 100%, 5 to 20% of the modified anti-friction and wear-resistant carbon fibers based on self-assembly, for example but not limited to 5%, 10%, 15% or 20%, etc., preferably 10 to 15%, more preferably 10%; 0 to 10% of polytetrafluoroethylene fibers, for example but not limited to 0%, 2%, 4%, 6%, 8% or 10%, etc.; and more than 70% of the epoxy resin matrix, for example but not limited to 70%, 75%, 80%, 85%, 90% or 95%, etc.

[0056] According to a specific embodiment of the fourth aspect of the present invention, the present invention provides a method for preparing the above-mentioned self-lubricating material containing modified fibers, which comprises the following steps:

[0057] The modified anti-friction and anti-wear carbon fiber based on self-assembly and the selectively added polytetrafluoroethylene fiber are mixed, and then added to a mixture of epoxy resin prepolymer and curing agent. After mixing evenly, the mixture is poured into a mold and cured to obtain the self-lubricating material containing the modified fiber.

[0058] In some embodiments, the epoxy resin prepolymer and the curing agent can be epoxy resin prepolymers and curing agents in the prior art, and the present invention does not specifically limit them. It can be understood by those skilled in the art that after the epoxy resin prepolymer and the curing agent react, an epoxy resin matrix is ​​formed. The mass ratio of the epoxy resin prepolymer and the curing agent can be conventionally adjusted by those skilled in the art, and can be 5:0.9 to 5:1.5.

[0059] In some embodiments, before pouring the uniformly mixed mixture into the mold, the mixture may be vacuumed to remove air bubbles therein.

[0060] In some embodiments, the curing includes two stages of curing, wherein the first stage of curing is performed at 60 to 100° C. for 2 to 5 hours, and the second stage of curing is performed at 100 to 140° C. for 2 to 5 hours.

[0061] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples and can of course be implemented with various modifications within the scope of the gist of the present invention.

[0062] Test method:

[0063] The mass ratio of carbon fiber and organic outer layer: obtained by thermogravimetric analysis (TGA). The specific testing method includes: using a TGA Q5000IR thermogravimetric analyzer, at a heating rate of 10°C / min and a test temperature of 25°C to 750°C, to perform thermogravimetric analysis on the modified carbon fiber sample to obtain a thermal weight loss curve; in the thermal weight loss curve, the ratio of the weight percentage of the modified carbon fiber sample at the weight loss inflection point (i.e., the weight percentage at the bottom of the inflection point) to the weight percentage lost at the weight loss inflection point is the mass ratio.

[0064] Carbon fiber diameter: obtained by observation under a scanning electron microscope (SEM). A certain number (e.g., more than 30) of carbon fiber samples need to be tested to obtain a diameter range.

[0065] Average thickness of the organic coating layer: obtained by transmission electron microscopy (TEM) observation. More than 5 points need to be randomly selected on the surface of each modified carbon fiber sample to test the thickness of the organic coating layer, and a certain number (for example, more than 30) of modified carbon fiber samples need to be tested, and the average value is taken to obtain the average thickness.

[0066] The molar ratio of cyclodextrin to dodecyl sulfate in the nanosheets formed by the cyclodextrin and sodium dodecyl sulfate is obtained by the amounts of cyclodextrin and sodium dodecyl sulfate used in the preparation method.

[0067] Planar size of nanosheets formed by cyclodextrin and sodium dodecyl sulfate: obtained by scanning electron microscopy (SEM) observation. It should be noted that the planar size of a nanosheet refers to the maximum straight-line distance between two points on the nanosheet. A certain number (e.g., more than 30) of nanosheet samples need to be tested to obtain the planar size range.

[0068] Thickness of nanosheets formed by cyclodextrin and sodium dodecyl sulfate: obtained by scanning with an atomic force microscope (AFM). A certain number (e.g., more than 30) of nanosheet samples need to be tested to obtain a thickness range.

[0069] Example 1

[0070] (1) 7.1 g of β-cyclodextrin and 0.9 g of sodium dodecyl sulfate (the molar ratio of the two is 2:1) are weighed and added to 18.7 g of deionized water, and stirred at 60° C. and 500 rpm for 12 h to allow cyclodextrin and sodium dodecyl sulfate to spontaneously assemble into a sheet structure, thereby obtaining a uniform, isotropic aqueous solution of self-assembled nanosheets with a mass fraction of 30%, and then freeze-drying the aqueous solution of the nanosheets to obtain nanosheet powder, and then using deionized water to prepare an aqueous solution of the nanosheet powder to obtain an aqueous solution of nanosheets formed by cyclodextrin and sodium dodecyl sulfate (SDS@2β-CD, abbreviated as SCD), wherein the concentration is 5 mg / mL; the nanosheets formed by cyclodextrin and sodium dodecyl sulfate (SDS@2β-CD) have a plane size of 1 to 15 μm and a thickness of 3 to 5 nm.

[0071] (2) The carbon fiber was ultrasonically treated in ethanol at 50°C for 3 h, and then the ethanol-treated carbon fiber was repeatedly washed with deionized water, and then vacuum dried at 100°C for 12 h to obtain desizing carbon fiber.

[0072] (3) 5 g of the desized carbon fiber (with a diameter of 5 to 10 μm) prepared in step (2) was immersed in 100 mL of an aqueous solution (5 mg / mL) of SDS@2β-CD prepared in step (1), and 100 mL of acetone was added dropwise thereto. The mixture was allowed to stand for 3 h to allow the SDS@2β-CD to spontaneously settle and precipitate on the surface of the carbon fiber to assemble into an organic coating layer. The product was then repeatedly washed with deionized water and then vacuum dried at 80°C for 12 h to obtain a modified antifriction and wear-resistant carbon fiber (CF-SCD) based on self-assembly.

[0073] The modified anti-friction and wear-resistant carbon fiber based on self-assembly includes: carbon fiber, and an organic coating layer formed on the surface of the carbon fiber, the organic coating layer includes nanosheets formed by cyclodextrin and sodium dodecyl sulfate; wherein the mass ratio of the carbon fiber to the organic coating layer is 9:1; and the average thickness of the organic coating layer is 50nm.

[0074] Figure 1 The SEM image of the desizing carbon fiber prepared in step (2) ( Figure 1 a1 in the figure), TEM image ( Figure 1 b1) in step (3) and the SEM image of the modified antifriction and wear-resistant carbon fiber based on self-assembly ( Figure 1 a2 in the figure), TEM image ( Figure 1 In b2), the difference in the carbon fiber surface before and after the organic coating layer is assembled can be clearly seen.

[0075] Figure 2The thermogravimetric graphs of desized carbon fiber (CF), modified antifriction and wear-resistant carbon fiber based on self-assembly (CF-SCD), and nanosheets SDS@2β-CD (SCD) formed by cyclodextrin and sodium dodecyl sulfate prove that the nanosheets formed by cyclodextrin and sodium dodecyl sulfate are successfully assembled on the surface of carbon fiber in this embodiment.

[0076] (4) Taking the total mass of the self-lubricating material containing the modified fiber as 100%, 10% of the modified anti-friction and anti-wear carbon fiber based on self-assembly and 10% of the polytetrafluoroethylene fiber are evenly mixed, and then the mixture is added to 80% of the mixture of E51 epoxy resin prepolymer and curing agent isophorone diamine, the mass ratio of epoxy resin prepolymer to curing agent is 5:1.2, and the mixture is stirred and mixed evenly, vacuumed to remove bubbles, and then poured into a silicone mold, cured at 80°C for 2h, then heated to 120°C, and continued to cure for 2h to obtain a modified anti-friction and anti-wear carbon fiber reinforced self-lubricating material based on self-assembly (EP+CF-SCD+PTFE).

[0077] Example 2

[0078] The difference from Example 1 is that in step (1), at 60°C, the aqueous solution of β-cyclodextrin and sodium dodecyl sulfate is stirred at a speed of 700 rpm for 12 hours, and the concentration of the prepared SDS@2β-CD aqueous solution is the same as that in Example 1; in step (3), the standing time is 4 hours. The rest is the same as Example 1. The planar size of the nanosheets formed by cyclodextrin and sodium dodecyl sulfate in this embodiment is 1 to 10 μm, and the thickness is 3 to 5 nm. The modified anti-friction and anti-wear carbon fiber based on self-assembly in this embodiment includes: carbon fiber, and an organic coating layer formed on the surface of the carbon fiber, the organic coating layer includes nanosheets formed by cyclodextrin and sodium dodecyl sulfate; wherein the mass ratio of the carbon fiber to the organic coating layer is 9.5:1; the average thickness of the organic coating layer is 45 nm.

[0079] The modified anti-friction and anti-wear carbon fiber based on self-assembly of this embodiment is used to prepare a self-lubricating material containing modified fibers, and the amount used and the preparation method are the same as those in Example 1.

[0080] Example 3

[0081] The difference from Example 1 is that in step (1), at 60°C, the aqueous solution of β-cyclodextrin and sodium dodecyl sulfate is stirred at a speed of 300 rpm for 12 hours, and the concentration of the prepared SDS@2β-CD aqueous solution is the same as that in Example 1; in step (3), the standing time is 2 hours. The rest is the same as Example 1. The planar size of the nanosheets formed by cyclodextrin and sodium dodecyl sulfate in this embodiment is 10-20 μm, and the thickness is 3-5 nm. The modified anti-friction and anti-wear carbon fiber based on self-assembly in this embodiment includes: carbon fiber, and an organic coating layer formed on the surface of the carbon fiber, the organic coating layer includes nanosheets formed by cyclodextrin and sodium dodecyl sulfate; wherein the mass ratio of the carbon fiber to the organic coating layer is 9.7:1; the average thickness of the organic coating layer is 40 nm.

[0082] The modified anti-friction and anti-wear carbon fiber based on self-assembly of this embodiment is used to prepare a self-lubricating material containing modified fibers, and the amount used and the preparation method are the same as those in Example 1.

[0083] Example 4

[0084] The difference from Example 1 is that the mass ratio of the carbon fiber to the organic outer layer in the modified anti-friction and anti-wear carbon fiber based on self-assembly is 10:1, and the average thickness of the organic outer layer is 40nm. In the preparation step, 5g of the desizing carbon fiber (with a diameter of 5 to 10 μm) prepared in step (2) is immersed in 100mL of an aqueous solution of SDS@2β-CD with a concentration of 3mg / mL prepared in step (1) (the preparation process of the nanosheet powder is the same as that in Example 1), and then 100mL of acetone is added dropwise thereto, and the remaining steps are the same as those in Example 1. The modified anti-friction and anti-wear carbon fiber based on self-assembly of this embodiment is used to prepare a self-lubricating material containing modified fibers, and the amount and preparation method are the same as those in Example 1.

[0085] Example 5

[0086] The difference from Example 1 is that the mass ratio of the carbon fiber to the organic outer layer in the modified anti-friction and anti-wear carbon fiber based on self-assembly is 8:1, and the average thickness of the organic outer layer is 60nm. In the preparation step, 5g of the desizing carbon fiber (with a diameter of 5 to 10 μm) prepared in step (2) is immersed in 100mL of an aqueous solution of SDS@2β-CD with a concentration of 6mg / mL prepared in step (1) (the preparation process of the nanosheet powder is the same as that in Example 1), and then 100mL of acetone is added dropwise thereto, and the remaining steps are the same as those in Example 1. The modified anti-friction and anti-wear carbon fiber based on self-assembly of this embodiment is used to prepare a self-lubricating material containing modified fibers, and the amount and preparation method are the same as those in Example 1.

[0087] Figure 3SEM images of modified friction-reducing and wear-resistant carbon fibers (Examples 1, 4 and 5) based on self-assembly obtained by assembling SCD aqueous solutions of different concentrations on the CF surface.

[0088] Example 6

[0089] The difference from Example 1 is that the molar ratio of β-cyclodextrin to sodium dodecyl sulfate is 1.8:1. In the preparation step, 6.1 g of β-cyclodextrin and 0.9 g of sodium dodecyl sulfate are weighed and added to 16.3 g of deionized water, and the remaining steps are the same as in Example 1. The concentration of the aqueous solution of SDS@2β-CD is the same as in Example 1.

[0090] The modified anti-friction and anti-wear carbon fiber based on self-assembly of this embodiment is used to prepare a self-lubricating material containing modified fibers, and the amount used and the preparation method are the same as those in Example 1.

[0091] Example 7

[0092] The difference from Example 1 is that the molar ratio of β-cyclodextrin to sodium dodecyl sulfate is 2.2:1. In the preparation step, 7.5 g of β-cyclodextrin and 0.9 g of sodium dodecyl sulfate are weighed and added to 19.6 g of deionized water, and the remaining steps are the same as in Example 1. The concentration of the aqueous solution of SDS@2β-CD is the same as in Example 1.

[0093] The modified anti-friction and anti-wear carbon fiber based on self-assembly of this embodiment is used to prepare a self-lubricating material containing modified fibers, and the amount used and the preparation method are the same as those in Example 1.

[0094] Example 8

[0095] The difference from Example 1 is that the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is different from that in Example 1. Based on the total mass of the self-lubricating material containing the modified fiber as 100%, the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is 5%, the amount of the polytetrafluoroethylene fiber is 10%, and the amount of the mixture of E51 epoxy resin prepolymer and curing agent isophorone diamine is 85%.

[0096] Example 9

[0097] The difference from Example 1 is that the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is different from that in Example 1. Based on the total mass of the self-lubricating material containing the modified fiber as 100%, the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is 15%, the amount of the polytetrafluoroethylene fiber is 10%, and the amount of the mixture of E51 epoxy resin prepolymer and curing agent isophorone diamine is 75%.

[0098] Example 10

[0099] The difference from Example 1 is that the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is different from that in Example 1. Based on the total mass of the self-lubricating material containing the modified fiber as 100%, the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is 20%, the amount of the polytetrafluoroethylene fiber is 10%, and the amount of the mixture of E51 epoxy resin prepolymer and curing agent isophorone diamine is 70%.

[0100] Embodiment 11

[0101] The difference from Example 1 is that polytetrafluoroethylene fiber is not added to the self-lubricating material containing modified fibers. In terms of mass percentage, the self-lubricating material containing modified fibers (EP+CF-SCD) of this example includes 10% of self-assembled modified antifriction and anti-wear carbon fibers and 90% of epoxy resin matrix.

[0102] Comparative Example 1

[0103] This comparative example is compared with Example 1, and the difference from Example 1 is that the self-lubricating material does not contain the modified anti-friction and anti-wear carbon fiber based on self-assembly. In terms of mass percentage, the self-lubricating material (EP+PTFE) of this comparative example includes 10% polytetrafluoroethylene fiber and 90% epoxy resin matrix.

[0104] Comparative Example 2

[0105] This comparative example is compared with Example 1, and the difference from Example 1 is that the modified anti-friction and wear-resistant carbon fiber based on self-assembly in the self-lubricating material containing modified fibers in Example 1 is replaced with unmodified desizing carbon fiber (prepared by step (2) of Example 1), and the dosage remains unchanged to obtain the self-lubricating material (EP+CF+PTFE) of this comparative example.

[0106] Comparative Example 3

[0107] This comparative example is compared with Example 1, and the difference from Example 1 is that the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is different from that in Example 1. Based on the total mass of the self-lubricating material containing the modified fiber as 100%, the amount of the modified anti-friction and anti-wear carbon fiber based on self-assembly is 2.5%, the amount of the polytetrafluoroethylene fiber is 10%, and the amount of the mixture of E51 epoxy resin prepolymer and curing agent isophorone diamine is 87.5%.

[0108] Comparative Example 4

[0109] This comparative example is compared with Example 1, and the difference from Example 1 is that instead of assembling SCD nanosheets on the surface of carbon fiber, polydopamine (PDA) nanosheets are grown in situ on the surface of carbon fiber to form an organic coating layer to obtain modified carbon fiber, which is then introduced into the epoxy resin matrix together with PTFE fiber. Specifically, the preparation method of the modified carbon fiber of this comparative example includes: dispersing 5g of desized carbon fiber (diameter 5-10μm) prepared in step (2) of Example 1 in 250mL of dopamine hydrochloride (0.5g) / Tris-HCl buffer solution with pH=8.5, stirring at a speed of 200rpm for 24h at room temperature, filtering the reaction mixture after completion of the reaction, and then repeatedly washing the product with deionized water, and then drying to obtain modified carbon fiber (CF-PDA). The SEM image of the modified carbon fiber is shown as follows Figure 4 The modified carbon fiber of this comparative example is used to prepare a self-lubricating material containing modified fiber, and the amount used and the preparation method are the same as those in Example 1.

[0110] Comparative Example 5

[0111] This comparative example is compared with Example 1. The difference from Example 1 is that sodium dodecyl sulfate is not added during the preparation of the nanosheets, and it is found that no nanosheets are prepared.

[0112] Comparative Example 6

[0113] This comparative example is compared with Example 11, and the difference from Example 11 is that no self-assembled modified anti-friction and anti-wear carbon fiber is added. Therefore, pure epoxy resin (EP) is prepared in this comparative example.

[0114] Comparative Example 7

[0115] This comparative example is compared with Example 11, and the difference from Example 11 is that the modified anti-friction and wear-resistant carbon fiber based on self-assembly in the self-lubricating material containing modified fibers in Example 11 is replaced with unmodified desizing carbon fiber (prepared by step (2) of Example 1), and the amount remains unchanged to obtain the self-lubricating material (EP+CF) of this comparative example.

[0116] Test Example 1

[0117] The self-lubricating materials provided in the above Examples 1 to 10 and Comparative Examples 1 to 4 were tested for friction and wear performance.

[0118] The self-lubricating material was tested by UMT-5 reciprocating friction and wear testing machine. The test conditions included: load of 10N, frequency of 5Hz, stroke of 3mm, test time of each sample of 1h, and repeated 3 times. The test results are shown in Table 1 and Figure 5 , Figure 6 As shown, Figure 5The friction curves of the self-lubricating materials with different CF-SCD contents (Comparative Example 1, Comparative Example 3, Example 1, Examples 8 to 10) are shown in Fig. Figure 5 a) and the average friction coefficient ( Figure 5 b) in the above, Figure 6 The friction coefficient of the self-lubricating material of Example 1 and Comparative Examples 1 to 2 shows that the self-lubricating material containing the modified anti-friction and wear-resistant carbon fiber based on self-assembly according to the embodiment of the present invention has a significantly reduced friction coefficient compared to the composite material without the modified anti-friction and wear-resistant carbon fiber of the present invention, the composite material with unmodified carbon fiber, the composite material with too little modified carbon fiber, and the composite material with carbon fiber modified with PDA nanosheets. The degree of reduction in friction coefficient can reach more than 50%.

[0119] The wear surface and wear volume of the wear scar after the friction test were observed by a three-dimensional white light interferometer, and the wear rate was calculated. The test results are shown in Table 1. Figure 7 , Figure 8 , Fig. 9 , Fig.10 As shown, Figure 7 is the average wear rate of the self-lubricating materials with different CF-SCD contents (Comparative Example 1, Comparative Example 3, Example 1, Examples 8 to 10), Figure 8 The three-dimensional white light images and wear scar depths of the surface wear scars of the self-lubricating materials with different CF-SCD contents (Comparative Example 1, Comparative Example 3, Example 1, Examples 8 to 10) are shown in FIG. Fig. 9 The wear scar morphology and depth of the self-lubricating materials of Example 1 and Comparative Examples 1-2 are shown in FIG. Fig.10 The wear rates of the self-lubricating materials of Example 1 and Comparative Examples 1 to 2 show that the wear scar depth of the composite material containing unmodified carbon fiber is large and very obvious, the wear scar of the composite material without carbon fiber is shallow, and the wear scar of the self-lubricating material containing the modified anti-friction and anti-wear carbon fiber based on self-assembly of the embodiment of the present invention is almost unobservable. By quantitatively calculating and comparing the wear rates, the self-lubricating material containing the modified anti-friction and anti-wear carbon fiber based on self-assembly of the embodiment of the present invention can reduce the wear rate by more than one order of magnitude compared with the composite material without the modified anti-friction and anti-wear carbon fiber; and, compared with the composite material with unmodified carbon fiber added and the composite material with too little modified carbon fiber added, the wear rate of the self-lubricating material containing the modified anti-friction and anti-wear carbon fiber based on self-assembly of the embodiment of the present invention is significantly reduced.

[0120] The calculation formula of wear rate Ws is: Where △V is the wear volume, F N is the normal load and d is the sliding distance.

[0121] Table 1

[0122]

[0123] It can be seen from Table 1 that the modified anti-friction and anti-wear carbon fibers based on self-assembly in the embodiments of the present invention significantly improve the overall anti-friction and anti-wear performance of the self-lubricating material.

[0124] Test Example 2

[0125] The self-lubricating materials and pure epoxy resins provided in the above Example 11 and Comparative Examples 6-7 were subjected to mechanical property tests, including bending, tensile and compression performance tests.

[0126] The bending performance can reflect the strength of the bonding between the fiber and the matrix, and the tensile and compressive performance can reflect the quality of the mechanical properties of the matrix. Fig.11 As shown, Fig.11 The bending properties of the self-lubricating materials and pure epoxy resins of Example 11 and Comparative Examples 6-7 ( Fig.11 a), tensile properties ( Fig.11 b) and compression performance ( Fig.11 c), it can be seen that the bending performance of the self-lubricating material containing the modified anti-friction and wear-resistant carbon fiber based on self-assembly of the embodiment of the present invention is improved, indicating that the interface bonding between the modified carbon fiber and the resin matrix is ​​improved; the tensile performance of the self-lubricating material containing the modified anti-friction and wear-resistant carbon fiber based on self-assembly of the embodiment of the present invention is slightly decreased, and the compression performance is slightly improved, indicating that the modified carbon fiber does not reduce the mechanical properties of the self-lubricating material. Therefore, while improving the anti-friction and wear properties of the self-lubricating material, the modified anti-friction and wear-resistant carbon fiber based on self-assembly of the embodiment of the present invention does not weaken the original mechanical properties of the self-lubricating material and the interface bonding between the carbon fiber and the resin matrix, but slightly improves the two.

Claims

1. A modified anti-friction and anti-wear carbon fiber based on self-assembly, comprising: Carbon fiber, and an organic coating layer formed on the surface of the carbon fiber, wherein the organic coating layer comprises nanosheets formed by cyclodextrin and sodium dodecyl sulfate; wherein the mass ratio of the carbon fiber to the organic coating layer is 8:1 to 10:

1.

2. The modified anti-friction and anti-wear carbon fiber based on self-assembly according to claim 1, wherein: The diameter of the carbon fiber is 5-10 μm.

3. The modified anti-friction and anti-wear carbon fiber based on self-assembly according to claim 1, wherein: The average thickness of the organic outer layer is 20-60 nm.

4. The modified anti-friction and anti-wear carbon fiber based on self-assembly according to claim 1, wherein: The molar ratio of cyclodextrin to dodecyl sulfate in the nanosheets formed by cyclodextrin and sodium dodecyl sulfate is 1.8:1 to 2.2:

1.

5. The modified anti-friction and anti-wear carbon fiber based on self-assembly according to claim 1, wherein: The nanosheet formed by the cyclodextrin and sodium dodecyl sulfate has a plane size of 1 to 20 μm and a thickness of 1 to 8 nm.

6. The method for preparing the modified antifriction and wear-resistant carbon fiber based on self-assembly according to any one of claims 1 to 5, comprising the following steps: The carbon fiber is immersed in a nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate, wherein the solvent in the nanosheet solution is a first solvent, which is a good solvent for the nanosheet, and then a second solvent is added dropwise, wherein the second solvent is a poor solvent for the nanosheet. The solution is allowed to stand, and the nanosheets formed by the cyclodextrin and sodium dodecyl sulfate spontaneously settle and precipitate on the surface of the carbon fiber, and assemble to form an organic outer coating layer, thereby obtaining the modified anti-friction and wear-resistant carbon fiber based on self-assembly.

7. The method for preparing the modified antifriction and wear-resistant carbon fiber based on self-assembly according to claim 6, wherein: The carbon fiber is desizing carbon fiber, and the desizing comprises: placing the carbon fiber in ethanol and ultrasonically treating it for 2 to 4 hours at 30 to 60° C., then washing the ethanol-treated carbon fiber with water, and then vacuum drying it at 80 to 120° C. for 12 to 24 hours to obtain the desizing carbon fiber.

8. The method for preparing the modified antifriction and wear-resistant carbon fiber based on self-assembly according to claim 6, wherein: The preparation steps of the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate include: adding cyclodextrin and sodium dodecyl sulfate into a first solvent, stirring, spontaneously assembling into nanosheets formed by cyclodextrin and sodium dodecyl sulfate, freeze-drying to obtain nanosheet powder, and then using the first solvent to prepare the nanosheet powder into a solution to obtain the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate; Preferably, the molar ratio of the cyclodextrin to the sodium dodecyl sulfate is 1.8:1 to 2.2:1; Preferably, the stirring conditions include: stirring at 40 to 70° C. and at a speed of 300 to 800 rpm for 12 to 24 hours; Preferably, the concentration of the nanosheet solution formed by cyclodextrin and sodium dodecyl sulfate is 1-6 mg / mL.

9. The method for preparing the modified antifriction and wear-resistant carbon fiber based on self-assembly according to claim 6, wherein: The mass ratio of the carbon fiber to the nanosheet formed by the cyclodextrin and sodium dodecyl sulfate is 5:(0.1-1.5); Preferably, the volume ratio of the nanosheet solution formed by the cyclodextrin and sodium dodecyl sulfate to the second solvent is 1:2 to 2:1; Preferably, the standing time is 2 to 8 hours.

10. A self-lubricating material containing modified fibers, comprising: 5-20% of the modified anti-friction and wear-resistant carbon fiber based on self-assembly as described in any one of claims 1-5, 0-10% of polytetrafluoroethylene fiber and more than 70% of epoxy resin matrix.

11. The method for preparing the self-lubricating material containing modified fiber according to claim 10, comprising the following steps: The modified anti-friction and anti-wear carbon fiber based on self-assembly and the selectively added polytetrafluoroethylene fiber are added to a mixture of epoxy resin prepolymer and curing agent, mixed evenly, poured into a mold, and after curing, the self-lubricating material containing the modified fiber is obtained; Preferably, the curing includes two stages of curing, the first stage of curing is curing at 60-100° C. for 2-5 hours, and the second stage of curing is curing at 100-140° C. for 2-5 hours.

Citation Information

Patent Citations

  • Solid olmesartan medoxmil dispersion and its prepn and medicinal application

    CN101066264A

  • Salt water etching resistant and stain resistant textile fabric and preparation method thereof

    CN113802366A

  • Bazedoxifene acetate oral instant tablet and preparation method thereof

    CN117398352A

  • Anti-friction and anti-wear high-temperature lubricating oil and preparation method thereof

    CN118580901A

  • System and method for manipulating nanotubes

    US6723299B1